PROMOTING RHEMA TOURS AND TRAVEL’S HOLYLAND TOURS USING A MARKETING BOOKLET - Natania Puspita; Jusuf I Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
Rhema Tours and Travel is a travel agency located in Jalan Jemursari 234A that specializes in Christian pilgrimage trips. It offers tours to Israel, Jordan, Egypt, and Europe. There were only a few people who know about Rhema Tours and Travel. This is probably due to ineffective promotional tools. Rhema Tours and Travel had brochures and company profiles to promote their Holy-land tours. However, those promotional tools are not very effective since they did not highlight the uniqueness of Rhema’s Holy Land Tours. Therefore, I made a marketing booklet to serve as an effective promotional tool that can promote Rhema’s Holy Land tours to customers by highlighting its uniqueness.